Eradication of Helicobacter pylori with first-line triple therapy, 10 days versus 14 days - Manrique-Lemus, María Nelly (2020)
Objective: To determine if the eradication rate of Helicobacter pylori with first line triple therapy for 14 days is better than with 10 days. Material and methods: Retrospective cohort study. It was reviewed medical records of the patients with dyspepsia and upper digestive endoscopy with a positive H. pylori biopsy, who received triple therapy with amoxicillin, clarithromycin and omeprazole for 10 or 14 days. Eradication was defined by the 13C-UBT breath test, 4 to 6 weeks after treatment. Results: It was evaluated 381 patients, 207 received treatment for 10 days and 174 for 14 days. The average age was 49 ± 13.9(15 to 82) years. The female sex was predominating (69,8%). The eradication rate of H. pylori in the 10-day and 14-day treatment group was 79, 7% and 82, 2% respectively (risk ratio, 1.03; 95% confidence interval, 0.94-1.14; p=0,541). Adverse events were reported in 75,1% and 77,3% of the 10 and 14 days group respectively (p= 0,634). Conclusion: First-line triple therapy for 14 days for H. pylori eradication was not better than 10 days’ therapy. The eradication rate was poor and unacceptable respectively.